BMP9 and BMP10 Act Directly on Vascular Smooth Muscle Cells for Generation and Maintenance of the Contractile State. Issue 14 (18th December 2020) - Wang, Lei; Rice, Megan; Swist, Sandra; Kubin, Thomas; Wu, Fan; Wang, Shengpeng; Kraut, Simone; Weissmann, Norbert; Böttger, Thomas; Wheeler, Matthew; Schneider, Andre; Braun, Thomas
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Vascular smooth muscle cells (VSMCs) show a remarkable phenotypic plasticity, allowing acquisition of contractile or synthetic states, but critical information is missing about the physiologic signals, promoting formation, and maintenance of contractile VSMCs in vivo. BMP9 and BMP10 (bone morphogenetic protein) are known to regulate endothelial quiescence after secretion from the liver and right atrium, whereas a direct role in the regulation of VSMCs was not investigated. We studied the role of BMP9 and BMP10 for controlling formation of contractile VSMCs. Methods: We generated several cell type–specific loss- and gain-of-function transgenic mouse models to investigate the physiologic role of BMP9, BMP10, ALK1 (activin receptor-like kinase 1), and SMAD7 in vivo. Morphometric assessments, expression analysis, blood pressure measurements, and single molecule fluorescence in situ hybridization were performed together with analysis of isolated pulmonary VSMCs to unravel phenotypic and transcriptomic changes in response to absence or presence of BMP9 and BMP10. Results: Concomitant genetic inactivation of Bmp9 in the germ line and Bmp10 in the right atrium led to dramatic changes in vascular tone and diminution of the VSMC layer with attenuated contractility and decreased systemic as well as right ventricular systolic pressure. On the contrary, overexpression of Bmp10 in endothelial cells of adult mice dramatically enhanced formation of contractile VSMCs and increased systemic blood pressure as well as right ventricular systolic pressure. Likewise, BMP9/10 treatment induced an ALK1-dependent phenotypic switch from synthetic to contractile in pulmonary VSMCs. Smooth muscle cell–specific overexpression of Smad7 completely suppressed differentiation and proliferation of VSMCs and reiterated defects observed in adult Bmp9/10 double mutants. Deletion of Alk1 in VSMCs recapitulated the Bmp9/10 phenotype in pulmonary but not in aortic and coronary arteries. Bulk expression analysis and single molecule RNA–fluorescence in situ hybridization uncovered vessel bed–specific, heterogeneous expression of BMP type 1 receptors, explaining phenotypic differences in different Alk1 mutant vessel beds. Conclusions: Our study demonstrates that BMP9 and BMP10 act directly on VSMCs for induction and maintenance of their contractile state. The effects of BMP9/10 in VSMCs are mediated by different combinations of BMP type 1 receptors in a vessel bed–specific manner, offering new opportunities to manipulate blood pressure in the pulmonary circulation.